ANALYSIS OF THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP ON TEACHER PERFORMANCE WITH INTRINSIC MOTIVATION AS AN INTERVENING VARIABLE IN TEACHERS LANGSA CITY STATE 4 HIGH SCHOOL - Imam Azra’I; Marbawi; Aiyub Yahya; Yusniar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study examines the influence of transformational leadership on teacher performance with intrinsic motivation as an intervening variable among teachers at SMA Negeri 4 Langsa City. This research uses a qualitative method and collects the data by distributing questionnaires to 49 respondents. Hypotheses were tested by using descriptive analysis techniques with SmartPLS 4.1.0.2 as the data processing tool. The results of this study show that (1) transformational leadership does not affect the performance of teachers at SMA Negeri 4 Langsa City, (2) transformational leadership has a significant positive effect on intrinsic motivation, (3) intrinsic motivation has a significant positive effect on teacher performance, and (4) transformational leadership does not affect teacher performance through intrinsic motivation as an intervening variable. The implications of this study are (1) high transformational leadership can affect teachers' intrinsic motivation and (2) transformational leadership is a determining factor in influencing teacher performance. Therefore, school principals must pay attention to teacher performance, namely intrinsic motivation and transformational leadership